Characteristics and Causes of Extreme Heavy Rainfall in Heilongjiang Province During August 2023 - Qi Duo; Wang Chengwei; Bai Xuemei; Gong Yanduo; Sun Qi; Luan Chen; Tang Kai; Zhao Yujie (应用气象学报)
From 2 August to 4 August in 2023, a prolonged and extensive extreme heavy rainfall event occurrs in the southeast of Heilongjiang Province. Utilizing multiple observations and ERA5 reanalysis data, characteristics of the precipitation process are analyzed focusing on large-scale circulation background, mesoscale circulation system evolution, environmental conditions from perspectives of climate statistics, weather analysis, and physical quantity diagnosis. Factors contributing to the prolonged extreme heavy rainfall event are explored. Main causes for the long duration of this heavy precipitation event are the stable maintenance of favorable large-scale conditions, such as the persistent divergence of the upper troposphere, the stable location of the west Pacific subtropical high (WPSH) and Northeast China cold vortex (NCCV), and continuous water vapor transport by the southwest jet. Due to the strong southwest jet, there is abundant moisture transfer, primarily through the advection of water vapor, which is the primary source for heavy rainfall. The process can be divided into two stages due to significant differences of rainfall, atmospheric stratification, and local circulation characteristics. In the first stage, the meridional water vapor inflow layer and the saturated layer are thick, resulting in high tropospheric humidity. The atmospheric condition is characterized by weak convective instability. Under the control of the northwest airflow at 500 hPa, the development of southwest jet, along with the influence of a weak eastward-moving vortex system at 850 hPa, results in horizontal wind speed convergence and systematic upward motion, leading to widespread and prolonged precipitation. The heavy rainfall area is mainly composed of cumulus embedded stratus, with a large coverage area of the cloud system, low echo centroid height, and high precipitation efficiency. With weak convective instability that promotes the development of convection and train effect in some periods, extreme hourly precipitation and large cumulative precipitation occur. In the second stage, the meridional water vapor inflow is concentrated in the lower troposphere with high intensity. The lower troposphere is close to saturation, with high humidity and temperature, while the middle and upper troposphere is dry and cold, and the atmospheric condition is more unstable than that in the first stage. Convection is developed and strengthened by the combined action of systematic uplift by a trough at 500 hPa, warm shear at 850 hPa, topographic convergence, and uplift. The cloud system is dominated by local strong cumulus clouds, and the distribution of precipitation intensity is uneven. At the beginning of this stage, convective cells continue to form at the trumpet-shaped terrain and move towards the eastern mountainous areas, organizing into linear convection. This is accompanied by the development and southward movement of surface convergence lines, leading to the generation of new convection and continuously causing localized intense short-duration rainfall.